Analysis on the effect of ZnO on Carbon nanotube by spray pyrolysis method - Ayeshamariam, A.; Saravanakkumar, D.; Kashif, M.; Sivaranjani, S.; Ravikumar, B. (Springer, 2016)
Background: ZnO/CNT nanocomposites were prepared using Zinc acetate source materials and with the assistance of copper plate, glycine and sugar solution. The combined behavior between these two materials may give rise to the production of advanced materials with a wide range of applications in electronics and optoelectronics. Methods: The ZnO-CNT nanostructures are successfully prepared by simple perfume spray pyrolysis method on copper substrate. The possible growth mechanism of ZnO-CNT nanocrystals formation by this method has been tried to explore the sensor and optical properties has been demonstrated. Results: The as-synthesized ZnO-CNT nanostructures were characterized using the scanning electron microscopy (SEM), transmission electron microscopy (TEM) and X-ray diffraction (XRD) pattern measured with Cu Kα radiation. Studies of the morphologies of the ZnO-coated CNTs revealed no significant change in the internal structures single walled graphite sheets and the diameters of the CNTs, but the ZnO appeared to form a layer of thinfilm single crystalline particles attaching to the surface of the nanotubes. The photoluminescence (PL) measurements excited by the 380 nm were done at room temperature. CNTs are easy to be entangled and agglomerate due to their long length and low diffusive mobility in base fluids. Conclusion: The lower mobility was found to occur for the ZnO/CNT composite where a linear sensitivity behavior was measured and it reaches high at the temperature of 200 °C. The samples luminescence is dominated by well-structured ultraviolet band emission and almost no deep level emission was observed, revealing a high optical quality of the produced structures.